Islamic Micro Enterprises; Constraints, Perceptions and Critical Issues - Hani, Syafrida; Irfan, Irfan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to describe how pmanagement practices that have been carried out by micro and medium enterprisesso far, and identifyvarious problems that become the main obstacles in implementing the concept of management and perceptions of micro, small and medium business managers on Islamic management. These results will be the basis for further researchin formulating a management model that is in accordance with governance entrepreneurial organization in an Islamic perspective, so that it is expected to increase business growth. The data collection process was carried out through library research and interviews with Muslim micro business management informants to identify problems. The results of the study are expected to contribute to minimizingThe problems faced include limited human resources, capital, low ability to manage finances, lack of innovation and mastery of information technology.